Ternary System of Pyrolytic Lignin, Mixed-Solvent and Water: Phase Diagram and Implications - Li, M.; Zhang, M.; Yu, Yun; Wu, Hongwei (American Chemical Society, 2018)
Bio-oil from biomass fast pyrolysis is considered as an important feedstock for the production of renewable fuels and green chemicals. Fast pyrolysis bio-oil generally contains water-soluble fraction, water-insoluble fraction (i.e., pyrolytic lignin, PL) and water in a single phase. However, phase separation can take place during bio-oil transport, storage and processing. In this study, a mixed solvent (MS) is developed based on the compositions of various fast pyrolysis bio-oils produced from a wide range of feedstocks and reactor systems. Experiments are then carried out to investigate the phase behaviour of the PL/MS/water ternary system. Several ternary phase diagrams are constructed for PL and its fractions, and the PL solubilities in various MS/water mixtures are also estimated. The PL solubility in the MS is high, i.e., ~112 g per 100 g of MS. In the PL/MS/water system, an increase in water content to ~17 wt % in the MS/water mixture leads to a slight increase in the PL solubility to a maximal value of ~118 g per 100 g of MS/water mixture, followed by a gradual decrease in the PL solubility when the water content further increases. It is found that the phase stability of the PL/MS/water system is strongly determined by the composition of the system. For example, the PL/MS/water system is always stable when the MS content is > 50 wt %, while the system is always phase separated when the PL content is > 54 wt %. A comparison of the results for various PL fractions indicates that the molecular weight of PL can affect the ternary phase diagram, with the PL of a lower molecular weight having a higher solubility in the same MS/water mixture. The presence of free sugar (i.e., levoglucosan, present in bio-oil as solute) also influences the ternary phase diagram of the PL/MS/system, but only at a low water content (i.e., < 20 wt %). The results suggest that such ternary diagrams may be potentially an important tool for predicting phase separation of bio-oil as results of changes in bio-oil chemistry in various processes (e.g., cold-water precipitation and ageing).